EVALUATION OF THE ACCURACY OF INSTAGRAM TRANSLATION FEATURE IN INTERPRETING ISLAMIC ARABIC POETRY - Al-Agil, Falen Hamzah; Imamuddin, Basuni (UI Scholars Hub, 2025)
This study focuses on evaluating the capabilities of Instagram translation feature in translating Arabic Islamic poetry, a literary genre rich in linguistic nuances and cultural context. Employing a qualitative methodology, this research conducts a comprehensive comparative analysis between the automatic translations produced by Instagram and manual translations done by experts. The findings reveal that, despite being useful, Instagram's translation feature often fails to fully capture the essence of Arabic Islamic poetry, with significant errors in understanding context and language nuances. These errors include inaccuracies in translating key words and difficulties in interpreting deeper meanings often closely tied to cultural and historical contexts. The study highlights the limitations of automatic translation technology when dealing with complex, layered texts, emphasizing the importance of additional resources such as manual translation and cultural knowledge in understanding poetry. The research recommendations stress using Instagram's translation feature as an initial tool for basic text comprehension, not as the primary source. These findings open an important discourse on the need to develop translation technologies more sensitive to cultural and linguistic contexts, as well as the importance of a more humane and contextual approach in the translation process. This research contributes significantly to the fields of applied linguistics, translation, and social media studies.